Is serum iron, iron binding capacity and ferrihn values indicated in determining the hepatocellular degenaration in patients with anti HCV positive hepatic inflammation - Yasemin KOŞAR; Ülkü DAĞLI; Senem KÜÇÜKBAŞ; Nurgül ŞAŞMAZ; Hülya ÖVER (Turkish Journal of Gastroenterology, 2020)
-